New Glucosamine Derivatives Based Reducing Disaccharides via Schiff Reaction - Ali Azeez, Jawaher; Salman, salih; Baqir Ali, Wassan (ASJ - Academic Science Journal, 2025)
Due to the importance of glucosamine, this project aims to improve its role in medicinal and pharmaceutical applications and find new derivatives derived from glucosamine with useful and beneficial applications. We planned to couple two important glucosamine compounds, 6-deoxy-6-amino-D-glucose and 2-deoxy-2-amino-D-glucose, with two reducing disaccharides (D-lactose and D-maltose) via Schiff coupling because the two compounds, glucosamine and reducing disaccharides, have the required function groups for the Schiff reaction: the amine groups and the aldehyde groups. The synthesis of a series of four compounds was performed and subjected to spectroscopic characterization to prove their structure and purity. The biological activity was tested for two compounds; one of them shows excellent activity toward two kinds of gram-negative and gram-positive bacteria, which cannot be killed by penicillin.